Effect of Yoghurt and Protexin Boost on Broiler Performance - Aftahi, A.; Munim, T.; Hoque, M.A.; Ashraf, M.A. (International Journal of Poultry Science, 2006)
The influence of yoghurt and protexin boost on broiler growth, feed intake, feed conversion ratio, livability and profitability production was studied from 1 to 35 days of age. A total of 120 day-old Arbor Acres commercial broiler chicks were distributed randomly into five dietary treatments. Each treatment had 3 replications each of 8 birds. The experimental treatments T1 considered as control and T2, T3, T4 received 3.0g, 4.0g, 5.0g sour yoghurt, respectively per liter of drinking water and T5 received 1.0g protexin boost per 10 liter of drinking water throughout the experimental period. Improvement was observed in body weight gain and feed conversion ratio of broiler of T5 group at 35 days of age compared to other groups. Satisfactory improvement was observed in birds of T4 treatment group. Diet of different treatments had no significant (p>0.05) effect on livability of broiler. It was concluded that yoghurt and protexin boost could show beneficial effect on broiler performance at the level tested and the inclusion of yoghurt at a level of 5 g per liter of drinking water could be economized broiler production.